Proliferating Pilar Tumors Are Characterized by Recurrent 15q, 6q, and 6p22.2 Alterations. (7th April 2023) - Fischer, Grant M.; Lindeman, Neal I.; Ligon, Azra H.; Russell-Goldman, Eleanor
Abstract: Proliferating pilar tumors (PPTs) are rare neoplasms of external root sheath derivation, which most commonly occur on the scalp of elderly women. Although typically showing classic histologic features such as trichilemmal type keratinization, a lobular architecture and peripheral palisading, squamous cell carcinoma (SCC) remains a common diagnostic pitfall. Therefore, we sought to explore the molecular pathogenesis of PPTs and compare it with that of cutaneous squamous cell carcinoma (cSCC). Herein, we describe the use of a next-generation DNA sequencing platform to provide the most comprehensive molecular genetic analysis to date of a cohort of 5 PPTs and compare them to 5 head and neck cutaneous SCCs. Recurrent broad arm-level gains of 15q and concurrent single-copy losses of 6q and 6p22.2 were observed in 4 of 5 (80%) PPT cases. Other recurrent mutations or alterations of significance were not found in PPTs. Notably, these chromosomal changes were not identified in any of the 5 cutaneous SCCs, which instead showed recurrent alterations in the known SCC driver genes TP53, CDKN2A, and NOTCH1 . Here, we show for the first time that PPTs are molecularly distinct from cutaneous SCC and provide evidence that recurrent alterations in chromosome 15 and chromosome 6 are central to the pathogenesis of PPTs.